Morphometric Differences in Body Dimensions of Local Goats Ladongi District, East Kolaka Regency - Badaruddin, Rusli; Indi, Amiluddin; Hadini, Hairil Adzulyatno; Aka, Rahim; Munadi, La Ode Muh (Universitas Labuhanbatu, 2022)
Goats are generally kept quite a lot and are livestock that have the potential to produce meat to meet protein of animal origin. This study aims to determine the difference between the body dimensions of local goats in Ladongi District, East Kolaka Regency with the research material of 165 Kacang goats and 121 Jawarandu goats. Peanut goats were divided into 3 age groups, namely (â‰¤12 months, 13-24 months, >24 months) each with 87, 46, 32 heads, and Jawarandu goats were divided into 3 age groups (â‰¤12 months, 13 months). -24 months, >24 months) each were 49, 33, 39 using a purposive sampling research method. Research parameters include the body measured includes body length, shoulder height, chest circumference, chest depth, hip height, hip width, and body weight. The data obtained were processed to obtain a correlation (r). The results showed that the age difference was very significant. The conclusion of the research variable that has the strongest correlation value in estimating body weight is chest circumference